Incomplete sensitivities in design and control of fluidic channels - Mohammadi, Bijan; Santiago, Juan (Computer Assisted Methods in Engineering and Science, 2023)
We would like to show how to perform shape optimization and state control at a cost comparable to the one of analysis. To this end, we propose to only use informations available for cost function evaluation and incomplete sensitivities not requiring the solution of the linearized state equation. The application of the method is presented for microfluidic MEMs design and control.